2021
DOI: 10.3390/su132212541
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Residents’ Support for Sustainable Tourism Development

Abstract: The tourism industry has been gravely affected by the COVID-19 pandemic. In this context, the purpose of this study was to explore residents’ support for sustainable tourism development in an integrative model that considered well-established factors and the impact of the COVID-19 pandemic. Addressing various research gaps caused by the pandemic, this study aimed to examine a model based on eight hypotheses. Using the premises of a cross-sectional study, data was gathered from residents from Sibiu. Data analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 84 publications
(341 reference statements)
0
12
0
1
Order By: Relevance
“…Joo et al (2021), for example, reported that residents are now more concerned about the health risks that tourist groups may bring to their regions than the economic benefits of tourism. Similarly, Vinerean et al (2021), who examined the perceptions of residents in Sibiu-Romania towards tourism, reported remarkable changes due to COVID-19. Residents now see tourists as actors that triggered the pandemic and forced the authorities to take new measures to curb the spread of COVID-19.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Joo et al (2021), for example, reported that residents are now more concerned about the health risks that tourist groups may bring to their regions than the economic benefits of tourism. Similarly, Vinerean et al (2021), who examined the perceptions of residents in Sibiu-Romania towards tourism, reported remarkable changes due to COVID-19. Residents now see tourists as actors that triggered the pandemic and forced the authorities to take new measures to curb the spread of COVID-19.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Tisca et al (2016) emphasized the need to focus on service quality (Stoleriu et al, 2019). Stoleriu et al (2019) reviewed the comments posted by tourists on Tripadvisor after visiting the Danube Delta, pointing out that the reviews relate to contact with nature and wildlife, their experiences being mostly passive, predominantly visual (Vinerean et al, 2021). During their undergraduate and/or master's studies, students spend between 4 and 6 years in Sibiu County, and this offered them the opportunity to visit the most famous holiday destinations in the surroundings of Sibiu.…”
Section: Q6-what Are the Most Famous Ecotourism Destinations In Romania?mentioning
confidence: 99%
“…The answers received regarding their visit in the last 2 years of the COVID-19 pandemic (Liu et al, 2021;Zhou et al, 2021;Ge et al, 2022;Mamirkulova and Mi, 2022) (Figure 6) show that, even during this period, the young people traveled. In a study published in 2021, Vinerean et al (2021) reported a decrease in the number of tourists from Sibiu to 59.23% in 2020 compared to 3.3.9 Q8-how many times have you visited the top 10 ecotourism destinations in Sibiu County?…”
Section: Q6-what Are the Most Famous Ecotourism Destinations In Romania?mentioning
confidence: 99%
“…Finally, from a gender perspective, we will also study the importance of networking as perceived by the advantages and disadvantages it involves. In fact, there are studies in the literature analysing people’s involvement in tourism activities during the Covid pandemic (Brouder 2020 ; Roman et al 2020 ; Vinerean et al 2021 ), but not referring to the specific case of rural tourism and also including the study of variables related to business management and gender. Among the variables related to business management considered in this study are specific training for carrying out tourism management activities and the processing of subsidies for the start-up of tourism activities by promoters.…”
Section: Introductionmentioning
confidence: 99%